Accounting Training and Mentoring “Accounting Goes to School” for High School Students in South Tangerang - Irma Paramita Sofia; Fitriyah Nurhidayah; Farhan Fadil Ghifari (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2026)
One of the key challenges we face in the modern era is the increasing openness not only in the movement of goods and services but also in the global labor market. Accounting knowledge is very important for personal life and future careers. Accounting knowledge is not only used for business purposes but also as a basis for effective calculations. However, not a few students, including college students, have difficulty learning accounting. The partner of this community service activity is SMA Yadika 5, South Tangerang. This activity was carried out to guide application-based financial accounting learning, and also to increase the understanding of financial accounting concepts, namely those of SMK Negeri 2 Pondok Aren South Tangerang, who participate in financial accounting tutoring activities.  Department of Accounting Universitas Pembangunan Jaya has carried out an activity devoted to the community. The material provided covers accounting practice questions, a finance-based application.